“Should I Stay or Should I Go?” Relationships Between Emotion Regulation and Basic Needs Satisfaction of Parents Displaced in Ukraine and Abroad (During the First 6 Months of The Russian Invasion of Ukraine) - Shyroka, Anastasiia; Senyk, Oksana; Zavada, Tetiana; Vons, Olena; Kornadt, Anna (Journal of Education Culture and Society, 2023)
Aim. The ability to regulate emotions depends on many factors, but for displaced persons, the satisfaction of basic needs is likely to be among the most important. Therefore, this study aimed at determining the degree of basic needs satisfaction and their relationship with indicators of emotion regulation in parents displaced within Ukraine and abroad due to the Russian invasion of Ukraine in 2022.Methods. The study sample comprised of parents (98% of whom were mothers), aged 18-55, who fled the war from 23 different regions of Ukraine to the safer Ukrainian regions (N = 99) or abroad (N = 241). Participants answered questions about their demographics, basic needs satisfaction, and emotion regulation.Results. There was no significant difference between parents displaced in Ukraine or abroad in access to basic resources, conditions of accommodation, medical care and emotional support, but parents abroad had better access to employment and education of their children. Parents in both groups had positive (refocused on planning, put the situation into perspective) and negative (rumination) strategies of emotion regulation. Parents who had higher level of their basic needs’ satisfaction, scored higher on positive emotion regulation strategies and were less likely to experience emotion regulation difficulties.Conclusion. Basic needs satisfaction can be considered an important protective factor for displaced persons’ emotional regulation. The obtained results allowed drawing of conclusions only about people who were able to participate in the study. The problem of access to a broader target population is discussed.